Vertical Stratification of Dissolved Organic Matter Linked to Distinct Microbial Communities in Subtropic Estuarine Sediments - Wang, Wenxiu; Tao, Jianchang; Yu, Ke; He, Chen; Wang, Jianjun; Li, Penghui; Chen, Hongmei; Xu, Bu; Shi, Quan; Zhang, Chuanlun (Frontiers in Microbiology, 2021)
Dissolved organic matter (DOM) provides carbon substrates and energy sources for sediment microbes driving benthic biogeochemical processes. The interactions between microbes and DOM are dynamic and complex and require the understanding based on fine-scale microbial community and physicochemical profiling. In this study, we characterized the porewater DOM compositions in a 300-cm sediment core from the Pearl River estuary, China, and examined the interactions between DOM and archaeal and bacterial communities. DOM compositions were highly stratified and associated with changing microbial communities. Compared to bacteria, the amplicon sequence variants of archaea showed significant Pearson correlations (r ≥ 0.65, P < 0.01) with DOM molecules of low H/C ratios, high C number and double bond equivalents, indicating that the distribution of archaea was closely correlated to recalcitrant DOM while bacteria were associated with relatively labile compounds. This is supported by the presence of auxiliary enzyme families essential for lignin degradation and bcrABCD, UbiX genes for anaerobic aromatic reduction in metagenome-assembled genomes of Bathyarchaeia. Our study demonstrates that niche differentiation between benthic bacteria and archaea may have important consequences in carbon metabolism, particularly for the transformation of recalcitrant organic carbon that may be predominant in aged marine sediments.